Tree growth descriptors of main late-flowering almond varieties in the Mediterranean basin - Arquero O.; Lovera M.; Salguero A.; Morales J.; Navarro A. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
This work studies vegetative habits at the end of the first growing year of almond trees that were not pruned. The following 12 late-flowering varieties were studied: 6 Spanish ('Antoñeta', 'Cambra', 'Glorieta', 'Guara', 'Marta' and 'Masbovera'), 3 Italian ('Cristomorto', 'Supernova' and 'Tuono') and 3 French ('Ferraduel', 'Ferragnès' and 'Lauranne'). The parameters analysed were growth habit, trunk diameter, height and width of the canopy and the ratio between canopy height and width. Most of the varieties showed a spreading growth habit. Only 'Antoñeta' was classified as weeping. Differences on vigour among the studied varieties were not relevant, only 'Marta' presents great vigour compared to the other varieties.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)